THE INFLUENCE OF ENTREPRENEURSHIP KNOWLEDGE, SELF-EFFICIENCY AND FAMILY ENVIRONMENT ON INTEREST IN ENTREPRENEURSHIP, STUDENTS OF THE FACULTY OF SOCIAL SCIENCES, JAKARTA STATE UNIVERSITY - Mardta, Rendy; Usman, Osly; Adha, Maulana Amirul (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This study aims to: 1) determine the effect of entrepreneurial knowledge on entrepreneurial interest; (2) regarding the effect of self-efficacy on the interest in entrepreneurship; (3) the family environment on the interest in entrepreneurship and (4) the influence of entrepreneurial knowledge, self-efficacy and the family environment on the interest in entrepreneurship. The population in this study were 207 students of the Faculty of Social Sciences, Jakarta State University, class of 2017 and 2018. In this research instrument, researchers used quantitative methods, as many as 136 respondents. data collection using a questionnaire. Data is processed using SPSS. The results of the research instrument show that entrepreneurial knowledge, self-efficacy and family environment have a significant effect on interest in entrepreneurship.